2015
DOI: 10.1080/19425120.2015.1094157
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Ecology of Juvenile Yellowfin Tuna from Waters Southwest of Taiwan Inferred from Stomach Contents and Stable Isotope Analysis

Abstract: The Yellowfin Tuna Thunnus albacares is one of the major fish species caught around subsurface fish aggregation devices (FADs) in the waters southwest of Taiwan. However, how it interacts with other organisms around FADs is poorly known. In this study, the diet and feeding habits of juvenile Yellowfin Tuna were estimated from the analysis of stomach contents from 1,477 specimens with FLs ranging from 24 to 108 cm and stable isotope analysis (202 specimens) collected around FADs in the waters southwest of Taiwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 74 publications
2
14
0
4
Order By: Relevance
“…Although several authors have reported the preference of yellowfin tuna for diverse fish families, the overwhelming contribution of flying fishes (Exocoetidae) found in this study were previously reported by Vaske‐Jr et al () and Ruderhausen et al () in the western Atlantic, and by Weng et al () from pre‐adults (90–110 cm in fork length) in the western Pacific, off Taiwan.…”
Section: Discussionsupporting
confidence: 43%
“…Although several authors have reported the preference of yellowfin tuna for diverse fish families, the overwhelming contribution of flying fishes (Exocoetidae) found in this study were previously reported by Vaske‐Jr et al () and Ruderhausen et al () in the western Atlantic, and by Weng et al () from pre‐adults (90–110 cm in fork length) in the western Pacific, off Taiwan.…”
Section: Discussionsupporting
confidence: 43%
“…, Weng et al . ) may indicate that these individuals were not from the population in Taiwanese waters.…”
Section: Discussionmentioning
confidence: 98%
“…Although samples from the western coast were limited, the distinct isotopic ratios, particularly those from Penghu, suggest that they were from a different, spatially segregated population than those individuals stranded or caught on the eastern or northern coasts. However, the comparable stable isotope ratios of plankton and cephalopods collected from the southwestern and southeastern waters of Taiwan (Tsai et al 2015, Weng et al 2015) may indicate that these individuals were not from the population in Taiwanese waters.…”
Section: Factors Affecting D 15 N and D 13 C Valuesmentioning
confidence: 99%
“…Weng et al . () also found evidence of a diet shift in juvenile T. albacares at c . 500 mm L F , to faster moving, surface‐associated prey.…”
Section: Discussionmentioning
confidence: 79%
“…Similarly, dietary shifts to a mesopelagic shrimp found at depths of 200–700 m and to a more piscivorous diet were documented, based on analyses of both stomach contents and stable‐isotope composition, in T. albacares juveniles, but at a larger size of c . 500 mm L F (B. S. Graham et al ., ; Weng et al ., ). B. S. Graham et al .…”
Section: Introductionmentioning
confidence: 97%